Safety and tolerability of theta burst stimulation vs. single and paired pulse transcranial magnetic stimulation: a comparative study of 165 pediatric subjects - Hong, Yaejee H.; Wu, Steve W.; Pedapati, Ernest V.; Horn, Paul S.; Huddleston, David A.; Laue, Cameron S.; Gilbert, Donald L. (Frontiers in Human Neuroscience, 2015)
Background: Although single- and paired-pulse (sp/pp) transcranial magnetic stimulation (TMS) studies are considered minimal risk in adults and children, the safety profile for theta-burst TMS (TBS) is unknown. Objective: In this comparative analysis, we explored the rate, severity, and specific symptoms of TMS-related adverse effects (AEs) between sp/ppTMS and TBS in subjects between ages 6 and 18 years. Method: Data from 165 participants from 2009-2014 were analyzed. Assessment of AEs was performed based on baseline and post-TMS administration of a symptom-based questionnaire that rated AEs on a 5-level ordinal scale (minimal, mild, moderate, marked, severe). AE rates and severity were compared using Chi Square or Fisher’s Exact Test depending on data characteristics. Result: Overall, no seizures or severe-rated AEs were reported by 165 pediatric participants. The rate of AE in all TBS sessions was 10.5% (n=76, 95% CI: 4.7 - 19.7%), whereas the rate of AE in all sp/ppTMS sessions was 12.4% (n=89, 95% CI: 6.3 - 21.0%). There was no statistical difference in AE rates between TBS and sp/ppTMS (p=0.71). In all sp/ppTMS and TBS sessions, 20 subjects reported a total of 35 AEs, among these 31 (~88.6%) were rated as “minimal” or “mild.” There was no difference in the severity of AE between TBS and sp/ppTMS (p=1.0). Only one of 76 TBS participants reported an AE rated as more than minimal/mild. Conclusion: Our comparative analysis showed that TBS appears to be as safe as sp/ppTMS in terms of AE rate and severity. This report supports further investigation of TBS in children.